An hepatitis B and D virus infection model using human pluripotent stem cell-derived hepatocytes - Chi, Huanting; Qu, Bingqian; Prawira, Angga; Richardt, Talisa; Maurer, Lars; Hu, Jungen; Fu, Rebecca Menhua; Lempp, Florian A.; Zhang, Zhenfeng; Grimm, Dirk; Wu, Xianfang; Urban, Stephan; et al. (EMBO reports, 2024)
Current culture systems available for studying hepatitis D virus (HDV) are suboptimal. In this study, we demonstrate that hepatocyte-like cells (HLCs) derived from human pluripotent stem cells (hPSCs) are fully permissive to HDV infection across various tested genotypes. When co-infected with the helper hepatitis B virus (HBV) or transduced to express the HBV envelope protein HBsAg, HLCs effectively release infectious progeny virions. We also show that HBsAg-expressing HLCs support the extracellular spread of HDV, thus providing a valuable platform for testing available anti-HDV regimens. By challenging the cells along the differentiation with HDV infection, we have identified CD63 as a potential HDV co-entry factor that was rate-limiting for HDV infection in immature hepatocytes. Given their renewable source and the potential to derive hPSCs from individual patients, we propose HLCs as a promising model for investigating HDV biology. Our findings offer new insights into HDV infection and expand the repertoire of research tools available for the development of therapeutic interventions.